Fault analysis on double three-phase to six-phase converted transmission line - Mustafa, M. W.; Ahmad, M. R.; Shareef, H. (IEEE, 2005)
High phase order transmission system is being considered a viable alternative for increasing the power transmission capability of overhead electric power transmission over existing right-of-way. This paper presents the faults analysis of six-phase transmission system. In this context, fault analysis has been conducted on the Goudey-Oakdale 2-bus test system. The results of these investigations are presented in the form of typical time responses. The PSCAD/EMTDC is used for the simulation studies.